Synthesis and characterization of regioselective substituted tetrapyridophenazine ligands and their Ru(II) complexes - Karnahl, Michael; Tschierlei, Stefanie; Kuhnt, Christian; Dietzek, Benjamin; Schmitt, Michael; Popp, Jürgen; Schwalbe, Matthias; Krieck, Sven; Goerls, Helmar; Heinemann, Frank Wilhelm; Rau, Sven (Dalton Transactions, 2010)
A series of novel regioselective substituted tpphz ligands and two novel mononuclear ruthenium complexes of the type [(tbbpy)(2)Ru(tpphzRn)](PF(6))(2) (where tbbpy = 4,4'-di-tert.-butyl-2,2'-bipyridine, tpphz = tetrapyrido[3,2-a:2',3'-c:3 '',2 ''-h:2''',3'''-j]phenazine, with n = 2 and R represents the bromine substituents at different positions) have been synthesized. All compounds were completely characterized by NMR and MS spectroscopy, absorption and steady-state emission spectroscopy as well as emission lifetime and electrochemical measurements. Additionally the solid-state structures of the two isomers [(tbbpy)(2)Ru(Br(2)tpphz)](PF(6))(2) 6 and [(tbbpy)(2)Ru(tpphzBr(2))](PF(6))(2) 7 are presented and compared with the results of density-functional theory calculations (DFT). Furthermore calculated Raman spectra were obtained by means of DFT calculations and used to assign the vibrational modes of the measured off resonance Raman spectra. A clear influence caused by the electronic effects of the different type and position of the substituents of tpphz on the photophysical behavior was observed.